Enhanced Documents of a Past Future: Re-interpretation of the Soviet History of Spaceflight in Contemporary Russian Blockbusters - Majsova, Natalija (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2019)
<span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">This article investigates the fictionalization of the space age in contemporary Russian spaceflight history blockbusters <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Gagarin: Pervyi v kosmose / Gagarin: First in Space <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">(2013), <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Vremia pervykh / Spacewalk <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">(2017), and <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Saliut<span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> 7 <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">(2017). This “second wave” of Russian films on spaceflight exhibits a greater affinity for the patriotic Soviet canon of portraying Soviet spaceflight history than their predecessors from the 2000s – <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Pervye na lune / First on the Moon<span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> (2004), <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Kosmos kak predchuvstvie / Dreaming of Space <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">(2005), and <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Bumazhnyi soldat / Paper Soldier <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">(2008) – which subverted the narrative conventions established by Soviet feature films on the history of spaceflight, i.e. their linearly progressive, normatively-optimistic plots, standard sets of historical characters, and common reliance on an authoritative third-person narrator. <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">The article argues that blockbusters of the past decade, in contrast, reinvent the patriotic Soviet narrative in a particular, (no(w)stalgic) way. Drawing on the discussion on the chronotope (Bakhtin) of outer space in Soviet and Russian cinema, this article explores the productions in question through the lens of their constructions of literal and metaphorical diagonality, verticality and horizontality. In doing so, it argues that the examined films embed historical events into fictional narratives and audio-visual worlds that monumentalise and mythologise the Soviet space age through the use of these spatial vectors, creating a novel, yet eerily familiar fictional collage of a past. <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Table of contents image from Saliut 7 (Klim Shipenko, 2017, Russia).